Management of Educational Facilities and Infrastructure: Efforts to Optimize the Learning Process at MA Nurul Fattah Lampung - Asep Irawan; Mela Apristianti; Lutfiatul Hidayah (Global Education Journal, 2026)
This research is motivated by the problem of the gap between infrastructure standard regulation and managerial practices in the field. At MA Nurul Fattah Lampung, facility management is still reactive and the inventory has not been digitized, so it often creates administrative obstacles that have the potential to reduce the quality of learning. The main objective of this research is to evaluate the practice of facilities and infrastructure governance in order to realize the optimization of a quality learning process. The method used was qualitative descriptive, with data collection through observation, in-depth interviews with seven key informants, and documentation studies. The results of the study found that empirically, well-maintained physical infrastructure transforms into a "living catalyst" that successfully increases teacher motivation and triggers pedagogical innovation in the classroom. However, the managerial implementation is still fragmented and the absence of standard Standard Operating Procedures (SOPs) often delays the achievement of curriculum targets. As a concrete recommendation, madrassas must immediately formulate and implement SOPs for infrastructure governance that are structured, proactive, and digitalized. This step is essential to prevent asset degradation, minimize inefficiencies, and ensure the sustainability of institutional excellence.